Improvement in surface morphology and mechanical properties of the polycaprolactone/ hydroxyapatite/ graphene oxide scaffold: 3D printing - salt leaching method - Shahrzad Shiran; Mohammad Sadegh Nourbakhsh; Mohsen Setayeshmehr; Seyed Ali Poursamar; Mohammad Rafienia (Journal of Materials Research and Technology)
Polycaprolactone and hydroxyapatite were used to fabricate bone scaffolds via 3D printing. Due to its superior characteristics in enhancing mechanical and biological properties graphene oxide (GO) was added to the ink. To control and achieve the optimized macro-micropores within the fabricated scaffold, 3D printing was accompanied by the salt leaching technique. Employing this modified method, the interconnectivity and roughness of the scaffold increased. PCL/HA scaffold containing NaCl was fabricated via 3D printing, with a speed of 2.0 mm/s and extrusion rate 4.3 × 10-3 g/mm. As followed by salt leaching to obtain a scaffold containing optimized macro-micropores. Optimized ink containing 50 (%w/w) salt with various GO concentrations (0, 0.25, 0.5, and 0.7 % w/w) were used before 3D printing of the scaffolds to adjust and enhance the mechanical and biological properties. The optimized scaffold with GO (0–0.7 % w/w), Young's modulus, and compressive strength increased from 9.2 ± 1 to 28.5 ± 0.5 MPa and 2.6 ± 0.9 to 10.62 ± 0.39 MPa, respectively. By increasing the GO, significant increase in cell viability (96 %–98 %) and ALP activity (0.49–0.57 IU/mg) on day 14 was observed. The results confirmed increases in wettability, bioactivity, cell viability, and cell attachment within PCL/HA/G0.5 % scaffold.